Estimates of Methane Release From Gas Seeps at the Southern Hikurangi Margin, New Zealand - Turco, Francesco; Ladroit, Yoann; Watson, Sally J.; Seabrook, Sarah; Law, Cliff S.; Crutchley, Gareth J.; Mountjoy, Joshu; Pecher, Ingo A.; Hillman, Jess I. T.; Woelz, Susi; Gorman, Andrew R. (Frontiers in Earth Science, 2022)
The highest concentration of cold seep sites worldwide has been observed along convergent margins, where fluid migration through sedimentary sequences is enhanced by tectonic deformation and dewatering of marine sediments. In these regions, gas seeps support thriving chemosynthetic ecosystems increasing productivity and biodiversity along the margin. In this paper, we combine seismic reflection, multibeam and split-beam hydroacoustic data to identify, map and characterize five known sites of active gas seepage. The study area, on the southern Hikurangi Margin off the North Island of Aotearoa/New Zealand, is a well-established gas hydrate province and has widespread evidence for methane seepage. The combination of seismic and hydroacoustic data enable us to investigate the geological structures underlying the seep sites, the origin of the gas in the subsurface and the associated distribution of gas flares emanating from the seabed. Using multi-frequency split-beam echosounder (EK60) data we constrain the volume of gas released at the targeted seep sites that lie between 1110 and 2060 m deep. We estimate the total deep-water seeps in the study area emission between 8.66 and 27.21 x 106 kg of methane gas per year. Moreover, we extrpolate methane fluxes for the whole Hikurangi Margin based on an existing gas seep database, that range between 2.77 x 108 and 9.32 x 108 kg of methane released each year. These estimates can result in a potential decrease of regional pH of 0.015-0.166 relative to the background value of 7.962. This study provides the most quantitative assessment to date of total methane release on the Hikurangi Margin. The results have implications for understanding what drives variation in seafloor biological communities and ocean biogeochemistry in subduction margin cold seep sites.